LED street lamp detection for automotive auto beam detection - Nurul Fadzlina, Jamin (2012)
As vehicle population increases, the number of road accidents also increases. Vital problems in transportation such as mobility and safety of transportation considered more, especially in metropolitans and highway. It is because of the reflection or refraction of light from different directions also contributed to this accident. Due from that, the driver could not identify the types of lamps in their environment whether it is street lamp or car lamp from others. When other drivers use the high beam from the opposite direction, will cause the view is blurred and glare. Due to that, many road users can be stuck with unintentional accident. The project of Light Emitter Diode (LED) Street Lamp Detection for Automotive Auto Beam Detection will be developed as addition features of the system to detect LED Street Lamp. Basically, this project is to differentiate between LED Street Lamp and car lamp to ignore LED noise when it is combined each other. The main purpose of this project is to enhance the automated high beam detection system using image processing technique in MATLAB, to detect LED street lamp for automated high beam detection and also to detect the vehicle-rear lamp within its proper distance for automated high beam detection. In order to implement this project, it was conducted with computer simulation (MATLAB) by using image processing method. There are two ways to identify the image or visual by its color or shape of the objects. My expected outcome is to develop the Graphical Using Interface (GUI) by taking the night vision images.